Analisis Desain Monster “XENO’JIIVA” dari Gim Monster Hunter World - Saputra, M Garry; Andelina, Ika Resmika (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2023)
Character design is a very important part of any storytelling media such as comics, novels, games, animation and the like because characters are the wheel of the whole story. A character design that has a well-thought-out and well-planned concept will certainly be more prominent and attractive compared to character designs that are instantly and haphazardly created. The focus of this research is the design of the dragon character in the Monster Hunter World game called Xeno'jiiva which was the best game in early 2018.The purpose of this research is to analyze the character design concept of Xeno'jiiva in the game Monster Hunter World with the aim of sharing knowledge about how we can design a character concept very creatively and without limits by using an intertextuality approach. This study uses a qualitative method with the approach of the paradigm matrix manga technique which is deepened by the holistic character design which is analyzed intertextually. With this research it is hoped that it can provide a better output in improving character design learning, so that in the future it can help develop the creative industries in Indonesia.